2023
DOI: 10.3390/pharmaceutics15071949
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Injectable Kartogenin-Conjugated Composite Hydrogel with a Sustained Drug Release for Cartilage Repair

Abstract: Cartilage tissue engineering has attracted great attention in defect repair and regeneration. The utilization of bioactive scaffolds to effectively regulate the phenotype and proliferation of chondrocytes has become an elemental means for cartilage tissue regeneration. On account of the simultaneous requirement of mechanical and biological performances for tissue-engineered scaffolds, in this work we prepared a naturally derived hydrogel composed of a bioactive kartogenin (KGN)-linked chitosan (CS-KGN) and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This suggests that the physical interactions between the PVA and Biobran in the core effectively slowed down the Biobran release from the nanofibrous scaffolds. 98–100 Notably, despite the higher hydrophilicity of B30 than B10 and B20, its Biobran release rate is comparatively slower. This can be attributed to its high crystallinity, small fiber diameter, and pore size, which also contributed to its enhanced stability during degradation.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the physical interactions between the PVA and Biobran in the core effectively slowed down the Biobran release from the nanofibrous scaffolds. 98–100 Notably, despite the higher hydrophilicity of B30 than B10 and B20, its Biobran release rate is comparatively slower. This can be attributed to its high crystallinity, small fiber diameter, and pore size, which also contributed to its enhanced stability during degradation.…”
Section: Resultsmentioning
confidence: 99%
“…found that due to the residual aldehyde groups within the oxidized sodium alginate (OSA) backbone, the composite CS‐KGN/OSA hydrogel also demonstrated attractive adhesive strengths in tissue applications owing to the generation of a number of Schiff base bonds between the aldehyde groups of the CS‐KGN/OSA hydrogel and the amine groups of the tissue. [ 58 ] In addition, Zhou et al. quantitatively evaluated the adhesive strength between the hydrogels and the tissue by SEM and burst adhesion testing, as shown in the following picture.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan conjugates show enhanced water solubility compared with unmodified CS and therefore are desirable for in vivo use. Chitosan conjugating with small-molecule drugs as PDCs for treating chronic inflammatory diseases has been extensively reported. …”
Section: Introductionmentioning
confidence: 99%